Impact Assessment of Agri-Clinic and Agribusiness Centres Scheme in Delhi (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The Agri-Clinic and Agribusiness Centres (AC&ABC) Scheme is a pivotal initiative launched by the Government of India in collaboration with NABARD to promote agripreneurship among agricultural graduates. The primary objectives of the scheme are to empower farmers, strengthen rural entrepreneurship, enhance agricultural extension services and facilitate effective technology transfer to improve agricultural productivity and profitability. The present study analyzes the performance of the AC&ABC scheme in Delhi based on year-wise, activity-wise and institute-wise indicators. The study relies on secondary data collected from annual reports, official websites such as MANAGE, NABARD and AC&ABC, along with research articles and journals. To examine the growth trend of trained candidates and establishment of agriventures, the Compound Annual Growth Rate (CAGR) method has been employed. The findings reveal that Delhi shows moderate performance under the scheme in terms of trained candidates and agriventure establishment. The maximum number of agricultural graduates were trained during 2011–12, while the highest number of agriventures were established in 2012–13. Agri-clinic services, agribusiness ventures and dairy/poultry-related enterprises emerged as the most successful activities. Among the training institutes, the Indian Society of Professionals demonstrated efficient performance, with most successful agriventures established by candidates trained under this institution. However, the overall performance of Delhi under the AC&ABC scheme remains limited. The CAGR of trained candidates was positive only during specific periods, while the growth rate of agriventure establishment remained low and negative in several years. The major reasons for low performance include limited awareness, inadequate outreach and lack of motivation among agricultural graduates. Therefore, to ensure effective implementation of the AC&ABC scheme, the government should strengthen promotional activities, provide better financial support and focus more on urban and peri-urban regions of Delhi to encourage agripreneurship and sustainable agricultural development.